Partisipasi dalam Promosi Kesehatan pada Kasus Penyakit Demam Berdarah (DB) Ditinjau dari Pemberdayaan Psikologis dan Rasa Bermasyarakat - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
Dengue Fever (DF) and its severeform, Dengue Haemorrhagic Fever (DHF), are major causes of morbidity and mortality for human beings. The cases of DF illness always increases in every year, especially when flood disaster occurred. Geographic position of Indonesia in tropical area made every province is DF endemic area. In 1997, there were 31.784 people and 156.697 people in 2007 who suffered from DHF. The Indonesian government conduct the community empowerment program as follows trainings for cadres of DHF prevention (Jumantik PSN DBD) in the communities and conduct the DHF prevention campaign in the schools in order to decreasethe casenumber of DHF patients. The aims of this research as follows: (1) to know the influence of the Psychological Empowerment to the Participation in Health Promotion on the Disease Case of DF